Mind-blowing music - Cox, Michael; Reeve, Philip (London : Scholastic, 1997)
Presenting a mind-blowing line-up of musical talent! Superstar Rock n' Roll legends Elvis, Chuck Berry, Little Richard! Cool classical megastars Mozart, Beethoven, Pavarotti! Mega pop legends The Beatles, The Sex Pistols, Oasis! AND many more special guests... Tune in to all sorts of COOL musical happenings, from the birth of the blues to the AMAZING invention of a sound recording machine. Get into the groove with MIND-BOGGLING musical instruments, and read about a tragedy that sparked the biggest MUSICAL EXPLOSION ever. PLUS how to become and overnight pop sensation! If you want to be in the know, get The Knowledge!
Keywords: History And Criticismmusic -- Music